2007
DOI: 10.1021/bi700291a
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Irreversible Coiled Coils in the Stalk Domain of ncd Motor Protein

Abstract: Ncd is a microtubule minus end-directed motor protein from Drosophila, a member of the kinesin-14 family, and an essential protein in mitosis and meiosis. Full-length ncd exists as a dimer via the formation of an alpha-helical coiled coil in its central stalk domain (P192-R346), which is thought to be one of the key regions for its motility. In our previous studies, however, none of the various synthetic polypeptide fragments (up to 46 residues) from the stalk domain formed a coiled coil. Herein, we have inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
(53 reference statements)
2
13
0
Order By: Relevance
“…Next, to verify the secondary structure of the purified polypeptides, we subjected them to Far-UV circular dichroism (CD) analysis, which is the appropriate secondary structure determination tool used for coiled-coil estimation [19], [38], [39]. The CD spectra of His-KLP68D/64D-S and His-KLP64D/68D-S heterodimers, collected in the P2 fractions, contained alpha-helical characteristic double minima at 208 and 222 nm (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Next, to verify the secondary structure of the purified polypeptides, we subjected them to Far-UV circular dichroism (CD) analysis, which is the appropriate secondary structure determination tool used for coiled-coil estimation [19], [38], [39]. The CD spectra of His-KLP68D/64D-S and His-KLP64D/68D-S heterodimers, collected in the P2 fractions, contained alpha-helical characteristic double minima at 208 and 222 nm (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in case of the X. laevis XCTK2, it has been demonstrated that, if the number of kinesins bound to microtubules is too high, gliding speed is significantly reduced, presumably owing to the non-synchronized state of multiple bound motors (Hentrich and Surrey, 2010). As mentioned previously, the presence of reversibly stable regions that can collapse in the coiledcoil domain (Hallen et al, 2008(Hallen et al, , 2011Ito et al, 2006;Makino et al, 2007) might be able to partially compensate for any braking that results from unsynchronized power force generation.…”
Section: Introductionmentioning
confidence: 91%
“…In Drosophila, the neck region at the proximal end of the coiled-coil stalk domain, adjacent to the motor, is essential for the regulation of lever-like rotations and step size (Hallen et al, 2011). Moreover, biochemical studies of Ncd stalk peptides (Ito et al, 2006) and additional studies (Makino et al, 2007) indicate the presence of sequence features that generate reversible and irreversible regions within the Ncd coiled-coil region. It has been proposed that a partial collapse of the Ncd stalk prevents braking that can occur when multiple Ncd motors are bound to a microtubule but without synchronized ATP hydrolysis and forcestroke generation (Makino et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] show that the two lever positions are each stabilized by multiple salt bridges and how the lever might be driven from one stable position to another is unclear. Furthermore, the lever (the coiled-coil tail of the motor) is potentially forbiddingly long: perhaps as long as 150 nm in the wild-type molecule, albeit with some regions less stable than others [7]. …”
Section: Structural Studies Reveal Two Stable Positions Of the Coiledmentioning
confidence: 99%